The Effect Of Aerobic Exercise On Fasting Blood Sugar As A Stroke Risk Factor: Pengaruh Latihan Aerobik Terhadap Gula Darah Puasa Sebagai Faktor Risiko Stroke - Indah Cahyani; Kurniawan, Ganesa Puput Dinda; Nasirudin, Yusuf (JURNAL PROFESIONAL FISIOTERAPI, 2024)
Introduction: A lifestyle that frequently consumes foods high in sugar and lack of physical activity can cause high blood sugar in the body, which can increase the risk factors for stroke. The physiotherapy intervention method that can be given to prevent the risk of stroke and reduce blood sugar is aerobic exercise. Method: This research is quasi-experimental with a two-group pretest-posttest with a control group design. The sample was selected using a purposive sampling method, and the number of samples for each group was 13 people in the aerobic exercise group and control group. The independent variable is fasting blood sugar as a risk factor for stroke, and the dependent variable is aerobic exercise. Blood sugar measurements were carried out using POCT at the beginning and end of the meeting session. Result: Testing with a paired sample t-test in the aerobic exercise group obtained a p-value of 0.000 (p<0.05), and then in the control group, a p-value of 0.537 (p>0.05) was obtained. The independent t-test showed that the p-value after the intervention was 0.000 (p<0.05). Conclusion: Providing aerobic exercise intervention is effective in reducing fasting blood sugar as a risk factor for stroke. Keyword: Aerobic exercise; Fasting blood sugar; Stroke risk factors.